Centralized Design and Analysis of Fiber Optic Communications on Universitas Garut - Sani Moch Sopian Sani; Dhami Johar Damiri Dhami; Folin Oktafiani; Mokhammad Mirza Etnisa Haqiqi; Tri Arif Wiharso (Telekontran : Jurnal Ilmiah Telekomunikasi, Kendali dan Elektronika Terapan, 2025)
In response to the increasing digital demands in higher education, this study investigates the design and feasibility of a centralized fiber optic communication system to support high-speed, reliable, and scalable network infrastructure at Universitas Garut. The proposed system replaces legacy copper-based and wireless networks that suffer from limited bandwidth and high signal loss, with a centralized topology using ITU-T G.652.D single-mode fiber to interconnect four campus buildings. A comprehensive design process was conducted, including route mapping based on GIS data, device selection, and technical performance analysis. Link budget and rise time budget calculations were performed to evaluate power losses, signal integrity, and feasibility over distances ranging from 1.4 to 2.14 km. Results show that received power levels across all routes remain significantly above the receiver sensitivity threshold of −24 dBm, with total losses under 13 dB, and rise time values under 40 ps, far below the 4501 ps limit for NRZ systems at 155.52 Mbps. These findings confirm that the proposed architecture ensures both signal strength and timing performance without the need for amplification or dispersion compensation. The system is proven technically feasible, cost-effective, and scalable to accommodate future digital services such as VoIP, CCTV, and campus-wide high-speed internet.